Firm‐specific forecast errors and asymmetric investment propensity. (21st October 2021) - Buchholz, Manuel; Tonzer, Lena; Berner, Julian
Abstract: This paper analyzes how firm‐specific forecast errors derived from survey data of German manufacturing firms over 2007–2011 relate to firms' investment propensity. Our findings reveal that asymmetries arise depending on the size and direction of the forecast error. The investment propensity declines if the realized situation is worse than expected. However, firms do not adjust investment if the realized situation is better than expected suggesting that the uncertainty component of the forecast error counteracts good surprises of unexpectedly favorable business conditions. This asymmetric mechanism can be one explanation behind slow recovery following crises.